DYNAMIC ASSESSMENT BASED MOBILE ASSISTED IN ARABIC LANGUAGE LEARNING - Musti’ah (Jurnal Penyelidikan Sains Sosial, 2020)
Some educational experts and practitioners argue that traditional assessment of language learning is still considered to be less able to develop student's (cognitive) potential since assessment with learning outcomes-oriented does not adequately describe the overall abilities of an individual, for instance, summative assessment. This article is intended to design a more innovative language assessment leading to an assessment for Arabic language learning through a mobile-assisted dynamic assessment for Indonesian Arabic speaking learners. Dynamic assessment (henceforth DA) is rooted in Vygotsky’s concept of zone proximal development (ZPD), which states student's learning potential can develop better through social interaction on a smartphone (WhatsApp). The DA process with smartphone-assisted devices can be carried out both inside and outside the classroom so that the learning process is flexible. The teacher can arrange learning time by a discussion with students when the DA process takes place. The current steps for implementing mobile-mediated DA in Arabic-speaking assessment are also presented in this paper